Projected Contributions of Nurse Practitioners and Physicians Assistant to Buprenorphine Treatment Services for Opioid Use Disorder in Rural Areas. (April 2020) - Andrilla, C. Holly A.; Patterson, Davis G.; Moore, Tessa E.; Coulthard, Cynthia; Larson, Eric H.
The United States is experiencing an opioid use disorder epidemic. The Comprehensive Addiction and Recovery Act allows nurse practitioners (NPs) and physician assistants (PAs) to obtain a Drug Enforcement Administration waiver to prescribe medication-assisted treatment (MAT) for opioid use disorder. This study projected the potential increase in MAT availability provided by NPs and PAs for rural patients. Using workforce and survey data, and state scope of practice regulations, the number of treatment slots that could be provided by NPs and PAs was estimated for rural areas. NPs and PAs are projected to increase the number of rural patients treated with buprenorphine by 10, 777 (15.2%). Census Divisions varied substantially in the number of projected new treatment slots per 10, 000 population (0.8-10.6). The New England and East South Central Census Divisions are projected to have the largest population-adjusted increase. NPs and PAs have considerable potential to reduce substantial MAT access disparities.